Higher education institutions: The synergies between total quality management and social responsibility - Nogueiro, T.; Saraiva, M.; Jorge, F. (EDULEARN21 Proceedings, 2021)
Total Quality Management (TQM) is an integrated management effort aimed at improving quality at any level to achieve excellence and corporate social responsibility (CSR), like most management concepts, has been gradually incorporated into the management practice of organizations. It’s important that in order to effectively manage socially responsible business, the organization needs to define strategies, programmes and action plans. CSR and TQM can improve the institution efficiency, reduce bureaucracy by eliminating duplication of policies and procedures and provide the alignment of goals and processes. There is a strategic influence of CSR in everyday practice of quality. The implementation of TQM systems can facilitate the incorporation of CSR objectives and practices by operating changes in organizational culture. Because of the environment and complex structure of higher education, quality measurement and management have given rise to a number of challenges. In a higher education institution, as in any other organisation, on the road to achieve excellence, there must be management commitment, support from administrative staff and teachers, effective and continuous communication, review, verification, validation and constructive alignment of processes. Quality indicators on sustainable development for education have been of growing interest and for this reason the possibility of creating a model that fits the reality of higher education integrating total quality and social responsibility should not be overlooked. Therefore, with this thought in mind, this work analyses the relationship or synergies between Total Quality Management and Social Responsibility themes not only associated to organisations but also associated to universities/higher education institutions.